Developing Pictorial Multiple Intelligence Inventory for Students - Musyarrafah Musyarrafah; Abdullah Pandang; Farida Aryani (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2019)
This study aims to (1) describe the need for pictorial multiple intelligence inventory for early grade students, (2) to find out the description of inventory forms, (3) to test usability, accuracy, and feasibility of the inventory, and (4) to know validity and reliability of the Inventory. The method of this research is a development research by using the research stages of Borg and Gall development research. Data is collected through interview, observation, and questionnaire, and the data were analyzed descriptively. The results showed that (1) inventory was needed by teachers and students in Darul Istiqamah Bongki, (2) The inventory was developed using orthogonal item extracts with alternative choices Yes and No. The inventory consists of eight sessions representing each Multiple Intelligences. (3) the results of expert validation tests show inventory products included in the criteria are very useful, very feasible and very appropriate. (4) the results of the validity test using Product Moment Correlation also show good validity on inventory, while the results of the reliability test with Cronbach Alpha show an alpha value of 0.729> 0.6 so that inventory has good reliability. This means that the substance of the Pictorial Multiple Intelligences Inventory developed has met the criteria of useful, feasible and appropriate, valid and reliable so that it can be used as a tool to map the plural intelligence of early grade students.